Clinical characteristics, diagnosis, and predictors of neurosyphilis patients with human immunodeficiency virus co-infection: A retrospective study at infectious diseases hospitals in two cities of China. Issue 42 (22nd October 2021) - Yu, Jianhua; Shi, JinChuan; Wan, Hu; Li, Jianwei; Shao, Ying; Ye, Jiangzhu; Dai, Lili; Wang, Xiwen; Liu, An
Abstract : Abstract: This study aimed to compare between the clinical and laboratory characteristics of neurosyphilis and those of syphilis in human immunodeficiency virus (HIV) positive and explore the risk factors associated with the occurrence of neurosyphilis in the HIV infected. In-patients diagnosed with HIV and syphilis co-infection who underwent a lumbar puncture and completed cerebrospinal fluid (CSF) examination were divided into neurosyphilis group and syphilis group. The demographic characteristics, symptoms and signs, and laboratory tests of the 2 groups were comparatively analyzed. Logistic regression analysis was used to explore the risk factors associated with the occurrence of neurosyphilis. Among 81 patients, 33 patients were assigned to the neurosyphilis group, and 48 to the syphilis group. There were no significant differences in the age, gender, marital status, acquired immunodeficiency syndrome course, opportunistic infections, serum HIV viral load, and history of syphilis treatment. The difference in HIV transmission route between the 2 groups was statistically significant ( P = .010), and the patients from the neurosyphilis group were mainly infected via heterosexual contact. The proportion of serum toludine red unheated serum test (TRUST) titer ≥1:16 in the neurosyphilis group were 78.8%, which was significantly higher compared to the syphilis group (48.9%). The level of CSF white blood cell count, CSF protein, and CSF HIV viral load in the neurosyphilis group were significantly higher than those of the syphilis group. The proportion of patients with neurological symptoms and signs in the neurosyphilis group was significantly higher compared to the syphilis group ( P < .001). Multivariate logistic regression analysis showed that heterosexual contact transmission route, not received antiretroviral therapy, lower CD4 cell count and higher serum TRUST titer, untreated with syphilis, and neurological symptoms and signs were risk factors associated with the occurrence of neurosyphilis. The serum TRUST titer, CSF white blood cell count, CSF protein level, CSF HIV viral load, and the percentage of neurological symptoms and signs in the neurosyphilis group were higher. Heterosexual transmission route, not received antiretroviral therapy, and untreated with syphilis prompted the possibility of neurosyphilis occurrence.